The Effectiveness of Retinalamin® Administered by Various Intramuscular Injection Timings in the Treatment of Patients with the Dry Form of Age- Related Macular Degeneration - V. V. Neroev; O. V. Zaitseva; T. D. Okhotsimskaya; I. V. Tsapenko; E. P. Lantukh (Российский офтальмологический журнал)
The paper presents the evaluation of Retinalamin efficacy administered intramuscularly to 90 patients (180 eyes) aged 47 to 75 (averagely, 65.9 ± 7.18 years) with various stages of dry age-related macular degeneration (AMD) once or twice in 6 months. The data of multifocal electroretinography (MfERG) showed that in 80 % of cases of early and intermediate AMD stages, the functional state of the retina improved after a course of Retinalamin, reaching a peak 2 months after the start of treatment. A second course of Retinalamin, given 3 months later, resulted in a more pronounced improvement of the functional parameters, achieving the maximum in the month 5 of the follow-up period. This is confirmed by a change in the P1 component of Mf ERG, which proved to be the most pronounced in the central ring, corresponding to the foveal area. In more than 70 % of cases with atrophic AMD, a positive dynamics of the functional activity of the macula was noted only after a repeated course of intramuscular injections of Retinalamin, whose curative effect reached the maximum in the month 5 of the follow-up. An increase in the density of the P1 component of MfERG was more noticeable in the last two rings, corresponding to the periphery of macula // Russian Ophthalmological Journal, 2016; 1: 39-46.